2014
DOI: 10.1038/srep04680
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of atherosclerosis by Helicobacter cinaedi infection that involves macrophage-driven proinflammatory responses

Abstract: Helicobacter cinaedi is the most common enterohepatic Helicobacter species that causes bacteremia in humans, but its pathogenicity is unclear. Here, we investigated the possible association of H. cinaedi with atherosclerosis in vivo and in vitro. We found that H. cinaedi infection significantly enhanced atherosclerosis in hyperlipidaemic mice. Aortic root lesions in infected mice showed increased accumulation of neutrophils and F4/80+ foam cells, which was due, at least partly, to bacteria-mediated increased e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 66 publications
2
43
0
Order By: Relevance
“…Although H. cinaedi infection was originally considered an opportunistic infection, some recent reports indicated the existence of H. cinaedi carriage in healthy persons (3)(4)(5). In addition, in these reports, the authors suggested the possibility of a close association between H. cinaedi and human diseases, such as atrial arrhythmia and arteriosclerosis, as well as human-tohuman transmission of this bacterium.…”
mentioning
confidence: 89%
“…Although H. cinaedi infection was originally considered an opportunistic infection, some recent reports indicated the existence of H. cinaedi carriage in healthy persons (3)(4)(5). In addition, in these reports, the authors suggested the possibility of a close association between H. cinaedi and human diseases, such as atrial arrhythmia and arteriosclerosis, as well as human-tohuman transmission of this bacterium.…”
mentioning
confidence: 89%
“…Additionally, a strong correlation has been observed between microbiota composition and AS development (5, 6). Infection of Helicobacter cinaedi was found to alter expression of cholesterol receptors and transporters in cultured macrophages and caused foam cell formation, and enhanced AS in hyperlipidemic mice (7). …”
Section: Introductionmentioning
confidence: 99%
“…Infection with Chlamydia pneumoniae (a pathogen isolated from coronary and carotid atheromatous plaques which plays an important role in cardiovascular disease [211] , hides inside apoptotic neutrophils to silently infect and propagate in macrophages [212] ) also induced macrophage-derived foam cell formation by upregulating ACAT1 expression and thus disturbed cholesterol homeostasis in these cells [213,214] . At present, one cannot exclude also a pathogenic role of Helicobacter cinaedi (one of the the most common enterohepatic Helicobacter species that causes bacteriemia in humans) infection in promoting atherosclerosis by involving macrophage-driven proinflamatory responses associated with TLR2 and TLR4 signaling, and causing foam cell formation [215] . Interestingly, Zhao et al [216] showed that hydrogen sulfide (H 2 S), a novel endogenous gasotransmitter and a well-known toxic gas with a characteristic smell of rotten eggs present also in drinking waters of wells and thermal spring and mineral waters, inhibited human monocyte-derived macrophage foam cell formation by suppressing ACAT1 production.…”
Section: Important Role Of Acat1 In Foam Cells Formation and Developmmentioning
confidence: 99%